Penyelesaian Sengketa Perjanjian Syariah pada Lembaga Keuangan Syariah - Herawan, Jajang; Anton , Mohamad (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Settlement of Sharia Agreement Disputes in Islamic Financial Institutions is a positive endeavor to provide legal certainty for justice seekers. The settlement of muamalah disputes in the Islamic tradition has been carried out since the time of the Prophet Muhammad. This is done through a court mechanism known today as litigation and through shulh, fatwa, tahkîm, mazhalim, and hisbah or what is known today as non-litigation. The forms of muamalah dispute resolution that operate in special Islamic financial institutions (LKS) that are currently in effect are almost the same as those that were in effect at the time of the Prophet. The path of litigation through the judiciary and the path of non-litigation through peace or alternative dispute resolution is known in fiqh as shulh, while the route through arbitration or in fiqh terminology is called tahkîm.